The Weaner Pig: Nutrition and Management. Proceedings of a British Society of Animal Science Occasional Meeting, University of 2001
DOI: 10.1079/9780851995328.0001
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the young weaned pig.

Abstract: Mathematical models for the assessement of growth in young weaned pigs are presented. Growth performance of piglets is analysed in relation to feed intake, gut capacity and weaning weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…This variation in pig growth performance both within and between litters continues through their lifetime (Kennedy, 1984). Growth rate is largely driven by feed intake (Whittemore and Green, 2001), hence variable growth rate is a reflection of variable feed intake. Research by Geary and Brooks (1998) has shown that each 50 g/day increase in dry-matter feed intake in the week following weaning was associated with an increase of 870 g in 28-day post-weaning weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation in pig growth performance both within and between litters continues through their lifetime (Kennedy, 1984). Growth rate is largely driven by feed intake (Whittemore and Green, 2001), hence variable growth rate is a reflection of variable feed intake. Research by Geary and Brooks (1998) has shown that each 50 g/day increase in dry-matter feed intake in the week following weaning was associated with an increase of 870 g in 28-day post-weaning weight.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and environmental factors contribute to variable feed intake within and between litters and herds of pigs. Environmentally, variable feed intake can be a result of, for example, birth weight, sex, weaning age, management system, disease status or diet composition (Pajor et al, 1991;Bruininx et al, 2001;Whittemore and Green, 2001;O'Connell et al, 2002). Profitability is also highly variable between herds -E-mail: elizabeth.magowan@afbini.gov.uk (Stein et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…At this time, the newly weaned pig encounters psychosocial and physical stressors including maternal and littermate separation, abrupt changes in diet and environment, and comingling and establishment of social hierarchy with unfamiliar pigs from different litters (11,46). In disease challenge models, it has been shown that the incorporation of weaning stressors is often required to initiate the development of enteric diseases, suggesting that stress plays a critical role in disease susceptibility (15,23).…”
mentioning
confidence: 99%
“…Kyriazakis and Whittemore (2006) suggested SM crit value of 0.032 for the industrial, standard pig house. The k value in this equation is about 0.05 (Edwards et al, 1988;Roan, 1991;Whittemore et al, 2001;Kyriazakis & Whittemore, 2006). This k value results in about 1 m 2 /100 kg of pig weight in the pen.…”
Section: Stocking Densitymentioning
confidence: 94%